5z+3=8z-4z

Simple and best practice solution for 5z+3=8z-4z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5z+3=8z-4z equation:


Simplifying
5z + 3 = 8z + -4z

Reorder the terms:
3 + 5z = 8z + -4z

Combine like terms: 8z + -4z = 4z
3 + 5z = 4z

Solving
3 + 5z = 4z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-4z' to each side of the equation.
3 + 5z + -4z = 4z + -4z

Combine like terms: 5z + -4z = 1z
3 + 1z = 4z + -4z

Combine like terms: 4z + -4z = 0
3 + 1z = 0

Add '-3' to each side of the equation.
3 + -3 + 1z = 0 + -3

Combine like terms: 3 + -3 = 0
0 + 1z = 0 + -3
1z = 0 + -3

Combine like terms: 0 + -3 = -3
1z = -3

Divide each side by '1'.
z = -3

Simplifying
z = -3

See similar equations:

| h=-16t^2+132t+5 | | 0=32t^2+12t | | 3(r+0.5)=r | | 5(x+4)+2x=3(5x-4)-10x | | y^8+8y^4+16=0 | | 1=7.5x | | 7w-4/3=-4/3w-3/4 | | 2n-5=7c | | 6+2(3x-1)=-8 | | 4xy+1=0 | | 6+2(3x-1)=8 | | 2-bracket(-5)= | | -3/10h=5 | | 18=(x*36)+(y*18) | | 7a-5+a-3-8a= | | 14v^8w^7x^5-28v^2w^8=0 | | 25j=5 | | 2r-9s=-73 | | 3(z+4)=9 | | 48-w=158 | | 3.14+3x=10 | | 5a-6-6a+4+a= | | 3p-4m-7= | | 3r-8s=-25 | | 7(40-x)=245 | | 5p+6=3p-8 | | 12-3=-13 | | 8y+11=3y+29 | | 9e-7=7-11 | | 9t-4a-4= | | f(y)=(4y^2/3-6y^4/3)^2 | | 1464÷3/4 |

Equations solver categories